Chemical changes in the composition of roasted kernels of Moroccan almonds - Kodad O.; Estopañán G.; Baddir K.; Juan T.; Sindic M.; Socias i Company R. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
The present work aims at determining the changes in the chemical components of almond kernels after roasting in pan with sand at during 25 min, as done in Northern Morocco. After roasting, oil content varied between 56% and 58.8%, protein content between 18.24% and 23.27%, and sugar content between 5.47% and 6.84%. These results show that the kernels maintain their nutritional value after roasting. Fatty acid composition was affected, with significant decreases in the percentage of palmitoleic, oleic and linoleic acids. The ratio of oleic to linoleic acids, a good index of resistance to rancidity, also decreased after roasting, although it was still similar to that of raw kernels of some commercial cultivars. The amount of the different tocopherol homologues was altered after roasting: α-tocopherol decreased, mainly in ‘Beldi’, characterised by low values before roasting, whereas in ‘Marcona’, with higher tocopherol concentration, the decrease was not so drastic. On the other side, γ-tocopherol increased in all samples after roasting. These results clearly show that the fatty acid profile and the tocopherol concentration are affected, but not drastically, by this roasting method. As a consequence, the quality of these roasted kernels is not significantly altered as compared to the raw kernels.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)